Drechslera avenae : quantificação da incidência e controle da transmissão de sementes para órgãos aéreos em aveia - Almeida, Mirella Figueiró de (2008)
Oat crop represented by Avena sativa and A. strigosa species, is one of the main alternative crops for farming during the winter in the South of Brazil. The fungus causal agent of oat helminthosporiosis is Drechslera avenae (Eidam) Sharif, which survives in seeds and in crop residues. Oat helminthosporiosis is present in all areas where the crop is cultivated. Its general occurrence is because the causal agent is in association with the seeds, being spread for long distances. When infected seeds are planted, the disease symptoms may be visualized in the coleoptyles or as lesions on plumules. This occurs, because the available methods of control are not enough to eradicate the pathogen from seeds. The objectives of the present work were: a) to screen an efficient method for detention of D. avenae in oats seeds; b) to quantify the incidence of the fungus in oats seeds in different counties of the Rio Grande do Sul state; c) to isolate, perform the pathogenicity test and to identify the causal agent; d) to develop a methodology for seed treatment aimed at to eradicate the fungus from infected seeds, to prevent the fungus transmission from seeds to the leaves. The experiments were conducted in the Laboratório de Fitopatologia of Faculdade de Agronomia and Medicina Veterinária of University of Passo Fundo. A total of 38 oats seeds samples were plated in gerboxes containing culture media and incubated in a growth room. The Reis selective medium was more sensitive in the detention of D. avenae and Alternaria alternate (Fr.) Keissler in white and black oats than the potato dextrose medium (PDA); for Bipolaris sorokiniana (Sacc.) Shoem., the PDA medium was the most sensitive in white oats, but for black oats there was no statistical differences between media